SUSTAINING EMPLOYEE PRODUCTIVITY DURING ECONOMIC TURBULENCE: THE EFFECT OF VIRTUAL OPERATIONS - Elikwu, Michael Ikechukwu; Erimafa, Monica; Johny, Friday Edet (Kashere Journal of Management Sciences, 2024)
This study investigated the moderating effect of virtual workplace operations on sustaining employee productivity during economic turbulence, with specific focus on sustainability of employee job involvement and productivity in private tertiary institutions in Abuja, FCT Nigeria. The cross-sectional survey design was adopted to support the collection of data with the aid of a structured 5-point Likert scale research instrument. The sample size of one hundred and seven (107) participants was adopted. In analysing the collated data, descriptive analytical methods, the Pearson Product Moment Correlation was employed to establish the relationship between the variables, while posited hypotheses were tested using the simple linear regression analysis. The findings revealed a positive and significant correlation between proxies of the independent variable and proxies of the dependent variable. This implies that, VOPS positively correlates to JBIN and positively correlates to PROD, both at 5% significant level respectively. This study therefore recommends that, management of these tertiary institutions should also put in place a system of periodic check on employees by heads of departments, to ensure optimal involvement of job roles within designated work periods and a review of policies supporting hours of virtual workplace operations, to help employees’ focus on full participation to achieve and sustain productivity in virtual operations